Agreement between competing tests for the identification of children with Developmental Coordination Disorder Concordância entre testes concorrentes para identificação de crianças com Transtorno do Desenvolvimento da Coordenação - Martins R.* (2020)
© 2020 Universidade Federal de Sao Carlos. All rights reserved.Objective: To verify the agreement of the results between different instruments, Movement Assessment Battery for Children - checklist and motor test (MABC-2) and Developmental Coordination Disorder Questionnaire (DCDQ-BR), used to indicate developmental coordination disorder (DCD). Method: A cross-sectional study, carried out in 2017, with data from seven to 10-year-old children from municipal schools in São José/SC. They were evaluated for motor performance using the MABC-2 (motor test and checklist) and DCDQ-BR instruments. The statistical analysis included the Kappa coefficient (K) to verify the agreement between the results of the instruments, considering a level of significance of 5%. Results: 302 children participated in the study, with a mean age of 8.5 ± 1.09 years old. When comparing the MABC-2 motor test, MABC-2 checklist, and the DCDQ-BR, we observed concordances from regular to weak (K = 0.303 / 0.116 / 0.039). Conclusion: The present study did not identify consistent agreement between the results of the MABC-2 and DCDQ-BR instruments for an indication of children with DCD, but their combination is a more complete form of evaluation.